Historical and Modern Perspectives on Mobile Labour: Parallel case study on Finnish and Estonian cross-border worker stereotypes and masculinities - Pirita Frigren; Keiu Telve (De Gruyter, 2022)
Parallels are drawn between representations of early 20th century Finnish maritime labourers on foreign merchant ships and present-day Estonian blue-collar commuter workers who work in the construction sector in Finland. We ask how the workers at both the times comment the media representations of them and how the possible analogues can be understood. The study focuses on two themes: stereotypes and masculinity ideals related to mobile work. The data comprise seamen’s letters, construction workers’ interviews, and media sources. By combining anthropological and historical analyses, we show that, rather than being occupation specific or related to time, certain features related to mobility, physical work, and gender tend to reappear in different kinds of circumstances. The features are characterised by the paradox of positive expectations and negative prejudices. We suggest that present-day discussions on cross-border work benefit not only from comparisons between different areas and occupations but also from historical juxtapositions.